2011
DOI: 10.1080/13501763.2011.544505
|View full text |Cite
|
Sign up to set email alerts
|

The European Union, multilateralism and the global governance of the Internet

Abstract: Social cues, such as eye gaze and pointing fingers, can increase the prioritisation of specific locations for cognitive processing. A previous study using a manual reaching task showed that, although both gaze and pointing cues altered target prioritisation (reaction times [RTs]), only pointing cues affected action execution (trajectory deviations). These differential effects of gaze and pointing cues on action execution could be because the gaze cue was conveyed through a disembodied head; hence, the model la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…To address the diversity of the actors participating and gain a perspective into the different types of organizations' distribution, we employ our relative openness measurement tool. In assessing hearings' relative openness, we note the contrast between the overall mean of different types of organizations invited and their distribution within each committee ( (Christou & Simpson 2006, 2011; underscored by the dominant presence of associations, and public interests in consumer affairs. For the validity of the analysis, due to the number of observations per category we grouped interest group types under three broader categories business, public interests, and research organizations.…”
Section: 1| Case Selection and Data Collectionmentioning
confidence: 99%
“…To address the diversity of the actors participating and gain a perspective into the different types of organizations' distribution, we employ our relative openness measurement tool. In assessing hearings' relative openness, we note the contrast between the overall mean of different types of organizations invited and their distribution within each committee ( (Christou & Simpson 2006, 2011; underscored by the dominant presence of associations, and public interests in consumer affairs. For the validity of the analysis, due to the number of observations per category we grouped interest group types under three broader categories business, public interests, and research organizations.…”
Section: 1| Case Selection and Data Collectionmentioning
confidence: 99%
“…In addition, authors have identified the EU's influence in uploading social aspects of its acquis commuataire into International Labor Organization (ILO) standards (Kissack 2011: 657). Others have identified EU influence in a wide range of other international regulatory arenas including the internet (Christou and Simpson 2011) and banking (Quaglia 2013). In addition, there has been considerable attention to the EU's performance in the Codex Alimentarius Commission, but, as I shall explore, the assessments of the EU's influence here are less favorable Hristova 2013;van Schaik 2013a: 111).…”
Section: Evidence Of Influence and Different Forms Of Regulatory Intementioning
confidence: 98%
“…The EU is placed within the context of a contested field; given the prominence of US‐based NGOs in the global governance regime of the internet (for instance, ICANN), the EU must negotiate with other global actors, most notably the USA. In some cases, stated EU aims and objectives have not been met, as EU agents have been rebuffed by their American counterparts (Christou and Simpson, 2011). This narrative, of a regional organization that is proactive in the politics of cyberspace is a common theme through the literature, notwithstanding some critiques (Guitton, 2013; Fahey, 2014; Sliwinski, 2014; Carrapiço and Barrinha, 2017; Christou, 2018).…”
Section: Literature Review: the Eu As An Emerging Cyber‐security And ...mentioning
confidence: 99%